Useful radio-pathological features for diagnosing ANCA-positive seroconversion in a patient with interstitial pneumonia. Issue 1 (2nd January 2018) - Yamakawa, Hideaki; Takemura, Tamiko; Yamanaka, Yumie; Tabata, Erina; Baba, Tomohisa; Ogura, Takashi
Abstract: We report a case of myeloperoxidase antineutrophil cytoplasmic antibody (MPO-ANCA) seroconversion with interstitial pneumonia that developed in a 67-year-old Japanese man. Radiological findings included a reticular shadow and cystic change along with increased attenuation in the lower lung. Histological findings revealed patchy dense fibrosis accentuated in the peripheral zones corresponding to a usual interstitial pneumonia pattern and marked inflammatory cell infiltration and cystic change, which indicated unclassifiable interstitial pneumonia. Although there was no evident reason to suspect connective tissue disease (CTD), because the above specific radio-pathological findings were obtained in our patient, we considered the possibility of interstitial pneumonia associated with CTD. We confirmed positive seroconversion of MPO-ANCA and diagnosed the patient as having MPO-ANCA-associated interstitial pneumonia. Therefore, anti-inflammatory therapy was initiated that resulted in improvement of our patient's respiratory symptoms and radiological findings. We report this valuable case because radio-pathological analysis may be a useful strategy enabling appropriate diagnosis of MPO-ANCA-associated interstitial pneumonia.